Protocol for the dano-run study: a 1-year observational follow up study on running related injuries in 1000 novice runners. Issue 4 (27th March 2011) - Nielsen, R; Ramskov, D; Sorensen, H; Lind, M; Rasmussen, S; Buist, I
Abstract : Background: The knowledge on the relation between running patterns and Running Related Injuries (RRIs) is sparse. Studies have tried to document a relationship. However, no firm conclusions can be made. Still it is necessary to identify which running exposures increase the risk of injuries and which exposures might be considered safe. Objective: The purpose of this study is to investigate the link between the running volume and the development of RRIs. Design: Observational prospective follow up study. Setting: Clinical setting on novice and recreational athletes. Participants: Healthy individuals (N=1000) who have not been running the past 1 year is included. All participants receive a global positioning system (GPS) watch (Garmin FR 110) and a pair of neutral running shoes (Adidas Glide 2). They are instructed to start running as much as they want, two times a week as a minimum. They must wear their GPS watch at each training session and upload data to an internet based database. All participants are followed for 1 year. Assessment of risk factors: Running volume measured as absolute number of kilometres and the graduation in kilometres pr. week over a period of 3 weeks. Main outcome measurement: RRI is defined as any musculoskeletal complaint of the lower extremity or back causing a restriction of running for at least 1 week. Results: Time to RRI is compared between groups with different absolute running volumes. In a similar way time to injury is compared between individuals with different weekly training graduations. Conclusion: This study may be the first study to adequately measure running patterns reliably in a large sample. The exposure is quantified by GPS, which is not affected by subject recall and is therefore a clear methodological improvement compared to previous studies. If absolute volume or running graduation over time seems to lead to injury, the study findings and methodology create a solid foundation for future randomised controlled trials in this field.